Epidemiology of donors and recipients: lessons from the SCANDAT database. (16th November 2017) - Edgren, G.; Hjalgrim, H.
SUMMARY: With the development of several 'vein‐to‐vein' databases, which capture data on the entire donor–recipient continuum and link this data to health outcomes, there has been an increasing number of studies investigating the health effects of all aspects of the practice of transfusion medicine. The Scandinavian Donations and Transfusions (SCANDAT) database is one of several such databases, which includes all electronically available data on blood donors, donations and transfusions since the late 1960s in Sweden and the early 1980s in Denmark. The SCANDAT database has been used to characterise disease occurrence among blood donors and transfused patients, as well as to investigate possible health effects of blood donations, aspects of transfusion care and possible transfusion transmission of disease. Recent publications include studies on recipient mortality associated with the storage lesion, studies on the effects of donor demographics on patient mortality and health effects of frequent blood donation. Although this research approach is clearly very powerful, the appropriate analysis of such real‐world data is complex and requires close methodological attention. The purpose of this review is to present some of the research conducted within the SCANDAT collaboration. We hope more international collaboration may help improve our understanding of the important remaining questions about donor and recipient health.